Learning Strategies Applied By Seventh Grade Students InLearning Writing At SMP N 3 Kartasura - Ariyani, Rusita Dewi, Aryati Prasetyarini, S. Pd, M. Pd (2017)
The study is aimed at describingthe learning strategies used by seventh grade students in learning writing. The object of the study in this research is language learning strategies used by the students in writingat SMP N 3 Kartasura. This research is qualitative research. The research uses learning strategies by O'Malley's Taxonomy consisting of metacognitive, cognitive, and socio-affective learning strategy. The subjects of the research are students of SMP N 3 Kartasura categorized into 2 categories, namely: S1 (high achievers) and S2 (low achievers) based on their ability in writing skill. The methods of collecting data are observation, interview, and document. In analyzing the data the writer takes the steps of reducing, explaining, and drawing conclusion.The result of this research shows that S1 (high achievers) used metacognitive strategy there are; advanced organizers, directed attention, elfmanagement, functional planning, self-monitoring, and self-evaluation. In cognitive strategy, they used repetition, translation, grouping, note taking, and contextualization. The last strategy used by S1 is soci-affective learning strategy which covers they used cooperation and question for clarification. The research shows that S2 (low achievers) use fewer number at learning strategies than S1 such as; metacognitive learning strategy, they used directed attention, delayed production, selective attention, and self-management. In cognitive strategy S2 used repetition, translation, deduction, keyword, note taking, and elaboration. In socio-affective learning strategy S2 uses cooperation and question for clarification.